Choices: safer partying using theatre-in-education. (7th October 2012) - Duncan, R; Graves, B; Wood, S
Abstract : Background: Local reports indicated high levels of risk-taking behaviour by young people while partying, especially when alcohol or other drugs were involved. Using theatre-in-education to improve young people's skills to keep themselves safer was shown to reduce the likelihood of harmful situations occurring. Aims/Objectives/Purpose: Raise young people's awareness and knowledge of how and why to choose safer partying behaviours. Increase parents' awareness of strategies to use in parenting. Support schools to provide related learning opportunities. Method: HYPE-GS collaboratively developed and delivered a performance for high-schools and alternative education centres, using a script based on local young people's stories of when partying 'went wrong'. An interactive 'Forum Theatre' component allowed audience members to rework characters' choices. Almost 2000 young people and over 200 parents saw the performances. We used a Logic Model planning process for programme and evaluation design. Data was collected through observation, questionnaires and interviews, to gauge the programme's effectiveness in raising awareness, increasing knowledge and changing behaviours. Results/Outcome: Interactive Forum Theatre engaged young people and contributed to awareness raising, attitudinal and potentially behavioural change in young people. Parents felt better informed of current partying issues and how they could be supported to deal with these. Significance/Contribution to the Field: CHOICES provided an innovative and engaging way of raising awareness of the potential harms of unsafe partying behaviours and allowed young people to explore alternative decisions that lead to better outcomes. The evaluation demonstrated the effectiveness of the process and made several recommendations for extending the programme reach.